Perbandingan Hasil Belajar Siswa yang Menggunakan Metode Mind Mapping dengan Siswa yang Menggunakan Metode Make A Match melalui Media Kartu dalam Pembelajaran Matematika - Yus Alkausela; Budi Mulyono (EduResearch Mitra Inovasi, 2020)
The problem of research is students mathematic learning outcomes who are using make a match method too low so as to work up it the reseacher apply to use mind mapping method. This research using card learning media on two methods so that learning can be easier. The purpose of research is informing about comparison two learning methods which can work up mathematics learning outcomes, the methods are mind mapping and make a match. The characteristic of research is true experimental with post test only control group design. The affordable population of this research is students of X UPW 1and X UPW 2 at SMKN 57 Jakarta for 2015/2016 academic year. The research’s sampling techniques using simple random sampling. Selected samples are 20 students for every class. Experiment class which using mind mapping learning method is X UPW 2 while control class which using make a match learning method is X UPW 1.The valid research instrument’s 27 items multiple choice. Requirements data analysis test consists of normality test using Liliefors test and homogeneity test using Fisher test. Result of requirements data analysis test are two class had normal distribution and homogeneous. Result of normality test for eksperimen class had L0 < Ltable (0,1552 < 0,190) and for control class had L0 < Ltable (0,1779 < 0,190) while result of homogeneity test had Fcount < Ftabel (1,07 < 2,168). Result of research hypothesis verify that average of students mathematics learning outcomes who are using mind mapping with card media significantly higher than students mathematics learning outcomes who are using make a match, because of tcount > ttable (4,55 > 1,686) so that H0 rejected dan H1 approved.